The influence of seasonal variations on yield components of sunflower - Hassan, Fayyaz-Ul; Ahmad, Rana Ashfaq; Qadir, Ghulam (Universiti Putra Malaysia Press, 2003)
The wider adaptability of the crop and wide range of climatic conditions of Pakistan make it possible to have two crops of sunflower in a year. Field experiments, one in spring and one in autumn were conducted at the University of Arid Agriculture, Rawalpindi, Pakistan to evaluate the influence of seasonal variation on yield and yield components of sunflower. Four sunflower hybrids were planted in randomized complete block design with three replications. Two central rows were harvested for the measurement of yield and yield components. It was observed that head size of spring crop was larger than autumn crop which was considered to be the result of overall better plant structure, length of crop life cycle, slow and gradual rise in cumulative degree days. Contrary to head size, thousand seed weight of autumn crop was found to be more than that of spring crop. Lesser seed weight of spring crop may be the result of competition for assimilates which left many seeds malnourished as larger head might have encouraged the initial setting of seeds. However, final yield of spring crop was greater than that of autumn crop. It led to the conclusion that having spring crop is the best option, however, autumn crop could be supplementary one to increase the production of oil seeds.